2017
DOI: 10.24198/jsk.v2i3.11964
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Riwayat Status Gizi Ibu Masa Keha milan dengan Pertumbuhan Anak Balita di Kecamatan Soreang Kabupaten Bandung

Abstract: Pertumbuhan saat balita memiliki dampak terhadap kehidupan selanjutnya karena masa balita merupakan masa kritis (golden period). Status gizi anak harus diperhatikan  sejak dalam kandungan. Asupan gizi yang baik pada saat kehamilan penting  untuk pertumbuhan janin sampai bayi dilahirkan. Bayi lahir dengan berat badan rendah dapat mengalami risiko gangguan pertumbuhan dengan gizi kurang, pendek dan kurus. Penelitian ini bertujuan untuk mengetahui hubungan riwayat status gizi ibu masa kehamilan yang dinilai denga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
3
8
0
9
Order By: Relevance
“…The study showed that the research subjects had a high awareness of routine antenatal care so that chronic energy deficiency could be immediately intervened with supplementary feeding (PMT). These results are also in line with Zaif et al (2017) and Prabandari et al (2016) which showed that there is no significant association between pregnant women and chronic energy deficiency with stunting (p = 0.218 and p = 0.376). Otherwise, a study conducted by Sukmawati et al (2018) showed a significant relationship (p= 0.01) between maternal nutritional status based on upper arm conference and stunting incidence, which happens because mothers with chronic energy deficiency had malnutrition state for a long time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study showed that the research subjects had a high awareness of routine antenatal care so that chronic energy deficiency could be immediately intervened with supplementary feeding (PMT). These results are also in line with Zaif et al (2017) and Prabandari et al (2016) which showed that there is no significant association between pregnant women and chronic energy deficiency with stunting (p = 0.218 and p = 0.376). Otherwise, a study conducted by Sukmawati et al (2018) showed a significant relationship (p= 0.01) between maternal nutritional status based on upper arm conference and stunting incidence, which happens because mothers with chronic energy deficiency had malnutrition state for a long time.…”
Section: Discussionsupporting
confidence: 91%
“…However, this study showed that there is no significant association between weight gain during pregnancy and stunting incidence. This research had similar results with some studies conducted by Zaif et al (2017) and Pusparini et al (2016) which also showed that there is no significant association between weight gain during pregnancy and stunting incidence (p values were 0.678 and 0.284, respectively). Differ from our result, Yudianti et al (2017) found that maternal weight gain during pregnancy and stunting incidence in children aged under five years was significantly associated (p= 0.031).…”
Section: Discussionsupporting
confidence: 90%
“…Salah satu dampak kekurangan zat gizi mikro pada masa kehamilan adalah anak lahir dengan berat badan rendah (BBLR) dan anak lahir pendek (stunting). 15 Hasil penelitian ini menunjukkan bahwa masih terdapat ibu hamil yang masuk dalam usia kehamilan berisiko, yaitu sebanyak 5,3 persen ibu hamil dengan usia di bawah 20 tahun dan 3,5 persen usia di atas 40 tahun (Tabel 1). Usia reproduksi yang sehat dan aman pada perempuan adalah usia 20-35 tahun.…”
Section: Pembahasanunclassified
“…Masalah gizi terutama stunting pada balita dapat mengganggu perkembangan anak, dengan dampak negatif yang akan berlangsung dalam kehidupan selanjutnya antara lain penurunan intelektual, rentan terhadap penyakit menular, penurunan produktivitas hingga menyebabkan kemiskinan dan resiko melahirkan bayi dengan berat lahir rendah. Selanjutnya dalam penelitian Zaif et al, (2017) bahwa status gizi ibu hamil sangat memengaruhi kondisi kesehatan dan perkembangan janin. Gangguan pertumbuhan dalam kandungan dapat menyebabkan lahir rendah.…”
Section: Gambar 1 Tim Pengabdian Kepada Masyarakat Dan Tim Posyandu Dari Kelurahan Tasikmaduunclassified